Implementasi Aplikasi Mading Berbasis Website Pada Fakultas Teknik Dan Komputer Universitas Harapan Medan - Dody Hidayat; Efri Riwandi; Ramli -; Liza Fitriana (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Wall magazines called Mading are one of the simplest types of written mass communication media. It is called a wall magazine because the basic principles of a magazine are dominant in it, while its presentation is usually attached to a wall or the like. Faculty of Engineering and Computer (FTK) Universitas Harapan (UnHar) Medan has several study programs: civil engineering, mechanical engineering, electrical engineering, informatics engineering, industrial engineering, information systems, and informatics management. FTK UnHar Medan in conveying information about academic and non-academic activities to students and other parties who need it is done by posting announcements on the campus Mading board, and this makes it challenging to obtain this information because students and parties who need it must come to campus and see directly on the Mading. From these problems, a study was conducted to design a website-based Mading application. The research used literature study, data collection, analysis, design, implementation, and system testing. The conclusion obtained from the final results of this study is to produce a website-based Mading application so that students and other parties who need information submitted by the campus, especially FTK UnHar, can be obtained quickly, accurately, and not limited by time because information can be accessed 24 hours online.